Validation of a commercial deformable image registration for surface‐guided radiotherapy using an ad hoc‐developed deformable phantom. Issue 12 (27th October 2020) - Pallotta, Stefania; Kugele, Malin; Redapi, Laura; Ceberg, Sofie
Abstract : Purpose: The use of optical surface systems (OSSs) for patient setup verification in external radiation therapy is increasing. To manage potential deformations in a patient's anatomy, a novel deformable image registration (DIR) tool has been applied in a commercial OSS. In this study we investigate the accuracy of the DIR as compared to rigid image registration (RR). Methods and Materials: The positioning accuracy of the DIR and RR implemented in the OSS was investigated using an ad hoc ‐developed anthropomorphic deformable phantom, named Mary. The phantom consists of 33 slices of expanded polystyrene slabs shaped thus to simulate part of a female body. Anatomical details, simulating the ribs and spinal cord, together with 10 inner targets at different depths are included in thorax and abdominal parts. Mary is capable of realistic body movements and deformations, such as head and arm rotations, body torsion and moderate breast/abdomen swelling. The accuracy of DIR and RR was investigated for four internal targets after deliberately deforming the phantom nine times. Breast and abdomen enlargements and torsions around x, y, and z axes were applied. For reference purposes, rigid displacements (where Mary's anatomy was kept intact) were included. The phantom was positioned on the linac couch under the OSS guidance and for each target and displacement a CBCT was acquired. The accuracy of DIR and RR was assessed evaluating the difference in means of absolute values between CBCT and the OSS registration parameters (lateral, longitudinal, vertical, rot, pitch, and roll), using both a reference surface extracted from CT (CTr) or acquired with the OSS (OSSr). A comparison of the four different combinations, DIR + OSSr, DIR + CTr, RR + OSSr, and RR + CTr, was carried out to evaluate the position accuracy for the various combinations. Finally, the positioning accuracy of the different target positions using only OSSr was investigated for the DIR. A paired sample Wilcoxon signed‐rank test ( P < 0.05) and a two‐tailed Mann–Whitney test ( P < 0.05) were carried out. Results: The DIR in combination with OSSr showed significantly ( P < 0.05) improved positioning accuracy in the lateral and longitudinal directions and in pitch, compared to RR, when deformations were applied to Mary. The positioning accuracy improved from 1.9 ± 1.5 mm, 1.1 ± 0.8 mm to 1.1 ± 1.2 mm, 0.6 ± 0.5 mm in lateral and longitudinal directions, respectively, and from 0.8 ± 0.6° to 0.4 ± 0.4° in pitch, using DIR compared to RR. Both the DIR and RR showed a similar positioning accuracy when rigid displacements of Mary were applied. For DIR, the OSSr generally showed improved calculation accuracy compared to CTr. Independent of the reference image used, the target position influenced the registration accuracy, and hence, one target could not be evaluated using RR due to its inability to calculate the correct position. Conclusions: Improved positioning accuracy was observed for DIR with respect to RR when deformations of Mary's anatomy were applied. For both DIR and RR, improved positioning accuracy was observed using OSSr as compared to CTr. The position of the target inside the phantom influenced the positioning accuracy for DIR.